News & Views - ., . (Journal of Engineering Education Transformations, 2010)
News: * National Conference on Revamping Teacher Education. * National Seminar on impact of globalization on higher education in India: opportunities and challenges. * National Seminar on Quality Education: Role of Teacher, Technology & Management. * International Conference on Education Informatics (EduMatics-201 0). on 22 May, 2010. organized by Chitkara Institute of Engineering and Technology, Rajpura (Punjab) and Indo-US Collaboration for Engineering Education (IUCEE). * The XII International Seminar will be held on broad theme "Globalization of Higher Education" from January 4-5,2011 at New Delhi, India. Views : * Quality Management of Technical Education in India. * Technical Education and TQM.